"Notional Grammar": Kausalitet i ESP - Andersen, Birger (HERMES - Journal of Language and Communication in Business, 1989)
The present paper describes the approach to language description and teaching known as "notional grammar" and argues that ESP research and teaching may benefit substantially from this approach, especially in the form proposed by Louis Trimble. The approach is illustrated by a research project which proposes to analyse the criteria for choice of textual and syntactic expressions of causality in ESP texts.